2022
DOI: 10.3390/ijerph19084878
|View full text |Cite
|
Sign up to set email alerts
|

Rural Household Differentiation and Poverty Vulnerability: An Empirical Analysis Based on the Field Survey in Hubei, China

Abstract: Rural family differentiation is an important perspective to analyze farmers’ behavior and poverty. Based on the data of 1673 farm households from rural field survey in 2019 in Hubei Province of China, this paper examines the main influencing factors of farm household differentiation on farm household poverty vulnerability from the perspective of the sustainable livelihoods of farm households. On this basis, the contribution of each influencing factor to farm household poverty vulnerability is analysed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…[ 16 ] As the age group increased, HPV increased, [ 52 ] whereas the education level acted the opposite. [ 52 , 53 ] A study [ 54 ] showed that household resource endowment and labor force, such as cultivated lands [ 55 ] and livestock raised, will decrease the risk of relative poverty. [ 54 ] Registered poor households and catastrophic medical expenses increased HPV, consistent with a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] As the age group increased, HPV increased, [ 52 ] whereas the education level acted the opposite. [ 52 , 53 ] A study [ 54 ] showed that household resource endowment and labor force, such as cultivated lands [ 55 ] and livestock raised, will decrease the risk of relative poverty. [ 54 ] Registered poor households and catastrophic medical expenses increased HPV, consistent with a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of urban–rural integration in China, with the rural market reform and the adjustment of agricultural industrial structure, the production behavior of farmers has changed from homogeneous pure farmers to heterogeneous non-farmers and part-time farmers, and the diversification of livelihood strategies [ 44 , 45 ] leads to the widening of the income gap between farmers. The boundary between the old generation of farmers and the new generation of farmers is increasingly clear [ 46 ]. At present, there is a phenomenon in China’s rural areas that “the post-1970s generation is unwilling to farm, the post-1980s generation will not farm, and the post-1990s generation will not talk about farming”.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, AMS not only replace labor input but also realize agricultural scale management through specialized division of labor and service aggregation. It helps low-income rural households to share the benefits of economies of scale, thereby narrowing the agricultural income gap with high-income rural households [ 28 ].…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%